An evidence-based approach to ending rural hunger - Homi Jamshed Kharas; John W. McArthur; Joachim von Braun (Kiel Institute for the World Economy (IfW), 2017)
Progress toward food and nutrition security (FNS) needs to be sharply accelerated in order to achieve the Sustainable Development Goal for ending hunger and malnutrition, especially in rural areas. The G20 should target interventions and investment opportunities to maximize impact on people and transformation of rural areas. Currently, few G20 countries map investments, technical assistance, capacity building and policy support in a data-driven way. Such tracking of needs, policies, and resources could include G20 countries' domestic efforts alongside countries they support with development assistance. The G20 could develop such a methodology to identify countries and interventions where additional resources could have a lasting impact. They could then systematically track and streamline FNS actions taken across international organizations and initiatives to efforts to help ensure the SDG is achieved.
Keywords: F01; F02; F35; F53; F63; Q18; 330; food security; rural hunger; data revolution; agriculture; G20